2009
DOI: 10.1007/s00442-008-1256-y
|View full text |Cite
|
Sign up to set email alerts
|

Non-lethal effects of an invasive species in the marine environment: the importance of early life-history stages

Abstract: 26Studies examining the effects of invasive species have traditionally focused on the 27 direct/lethal effects of the invasive on the native community but there is a growing 28 recognition that invasive species may also have non-lethal effects. In terrestrial 29 systems, non-lethal effects of invasive species can disrupt early life-history phases 30 (such as fertilization, dispersal and subsequent establishment) of native species but in 31 the marine environment, most studies focus on adult rather than early l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 63 publications
0
23
1
Order By: Relevance
“…Larvae of both species settled gregariously (Microcosmus squamiger only so at the highest concentration tested), and showed more random settlement in the presence of larvae of the other species. In contrast to our results, Rius et al (2009a) found that the settlement success of M. squamiger in its native Australian range was negatively affected by previously settled recruits of the introduced Styela plicata and vice versa. We expected some kind of interference effect as both species form dense aggregations in nature on artificial man-made substrata, so that competition for space is likely to be strong between them.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…Larvae of both species settled gregariously (Microcosmus squamiger only so at the highest concentration tested), and showed more random settlement in the presence of larvae of the other species. In contrast to our results, Rius et al (2009a) found that the settlement success of M. squamiger in its native Australian range was negatively affected by previously settled recruits of the introduced Styela plicata and vice versa. We expected some kind of interference effect as both species form dense aggregations in nature on artificial man-made substrata, so that competition for space is likely to be strong between them.…”
Section: Discussioncontrasting
confidence: 56%
“…This process did not seem to act in the present work. In previous experiments with the same species used here, Rius et al (2009a) first exposed eggs of M. squamiger in its native range (Australia) to the sperm of introduced S. plicata, then the eggs were washed, and finally exposed to conspecific sperm. That study found no effects of the heterologous sperm on the fertilization process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this may seem to be a short time frame to measure offspring performance, a previous study on Styela plicata at the same field site showed that 99% of all post-settlement mortality occurred within the first two weeks after settlement (Rius et al 2009). Although this may seem to be a short time frame to measure offspring performance, a previous study on Styela plicata at the same field site showed that 99% of all post-settlement mortality occurred within the first two weeks after settlement (Rius et al 2009).…”
Section: Post-metamorphic Survivalmentioning
confidence: 99%
“…It can compete and displace native species (Rius et al 2009b). It is one of the most common harbour ascidian species worldwide (Lambert and Lambert 2003;Rocha and Kremer 2005;Wyatt et al 2005).…”
Section: Styela Plicata (Lesueur 1823) Introducedmentioning
confidence: 99%